Social formations of early South India - Rājangurukkaḷ (Oxford University Press, 2010., 2010)
An examination of the the socio-economic and political processes in south India from ancient to early medieval period. It covers various aspects of social formations in south India-economy, technology, social relations, institutions, agrarian structure, political processes, state, writing, and so on. The collection is broadly organized into four parts viz., the methodological perspectives, pre-historic formations, Read more...